Perinatal outcomes and offspring growth profiles in twin pregnancies complicated by gestational diabetes mellitus: A longitudinal cohort study. (January 2021) - Mei, Youwen; Yu, Jiaxiao; Wen, Li; Fan, Xin; Zhao, Yan; Li, Jie; Qiao, Juan; Fu, Huijia; Leong, Pamela; Saffery, Richard; Tong, Qi; Kilby, Mark D.; et al.
Highlights: GDM complicated MCDA pregnancies are associated with increased risk of GHD. GDM is associated with decreased risk of fetuses being SGA in MCDA pregnancies. Twins of GDM pregnancy have higher risk of overweight at 6 months of corrected age. Abstract: Aims: To evaluate the influence of gestational diabetes mellitus (GDM) on the perinatal outcomes of twin pregnancies and its impact on fetal growth profiles of twin offspring from 6 weeks to 12 months of corrected age. Methods: A longitudinal cohort study was conducted among pregnant women with twins and their twin offspring. All information on perinatal outcomes and child growth trajectories from 6 weeks to 12 months of corrected age were obtained and analyzed using a general linear model and logistic regression models. Results: GDM was not correlated with adverse perinatal outcomes of twin pregnancies; however, in monochorionic diamniotic (MCDA), but not dichorionic diamniotic (DCDA) twin pregnancies, GDM was correlated with gestational hypertension disorder and a fetus being small for gestational age (OR, 2.68; 95% CI 1.16–6.04 and OR, 0.35; 95% CI 0.16–0.76, respectively). In both MCDA and DCDA groups, GDM was positively associated with a higher risk of childhood overweight at 6 months of corrected age (2.32 [1.05, 5.09] and 2.00 [1.13, 3.53]). Conclusions: GDM had a greater impact on MCDA twin pregnancies in terms of maternal gestational hypertension disease and small for gestational age of newborns. Additionally, twin offspring exposed to GDM had a higher risk of being overweight at 6 months of corrected age irrespective of chorionicity. Clinical Trial Registration: ChiCTR-OOC-16008203.